The Incidence of Child Health Improvements. Issue 2 (19th May 2016) - Sahn, David E.; Younger, Stephen D.
Abstract: Economic growth accelerated during the first decade of the 2000s in many poor countries, especially in Africa. This welcome news is widely discussed, even in the popular press. Yet as economies grow, some analysts express concerns that such growth is not having as significant an impact on poverty as one would hope. Analysts and policymakers ask whether this growth is adequately pro‐poor, shared, or inclusive. Less noticed is that improvements in children's health are accelerating, too. This paper examines the extent to which these health improvements are equitably shared or "inclusive." We use a descriptive method, which is analogous to growth incidence curves, and apply it to eight countries from Africa, Asia and Latin America. We draw two principal conclusions. First, within countries, health improvements often have a different distribution than income/expenditure growth, and that distribution is usually more hopeful in the sense that it is more likely to be strongly pro‐poor than the distribution of income growth. Second, we have yet to see clear patterns in terms of the within‐country relationship between growth incidence curves and health improvement incidence curves. Thus, one cannot rely on the information in the growth incidence curve to infer the inclusiveness of health improvements.